Mitochondrial genome instability: its potential role in biomarker discovery for brain tumorigenesis - Yusoff, Abdul Aziz Mohamed (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Background: Mitochondria are major cellular sources of reactive oxygen species (ROS) generation which can induce mitochondrial DNA (mtDNA) damage and lead to carcinogenesis. MtDNA 4,977-bp deletion as well as alteration in mtDNA copy number have been implicated in various types of human cancers. The aim of the present study was to find out the association of mtDNA 4,977-bp deletion and mtDNA content in brain tumor from the Malaysian patients. RU GRANT FINAL REPORT FORM (An abstract of between 100 and 200 words must be prepared in Bahasa Malaysia and in English. This abstract will be included in the Report of the Research and Innovation Section at a later date as a means of presenting the project findings of the researcher/s to the University and the community at large) Project Code (for RCMO use only) Account Number: 1001 / PPSP/812110 Methods: Brain tumor tissues and corresponding blood specimens were obtained from 50 patients. For comparison, 40 blood samples of healthy controls were also included in this study. The mtDNA 4,977- bp deletion was detected using the multiplex Polymerase chain reaction (PCR) analysis and later was confirmed by direct DNA sequencing. Furthermore, the mtDNA content was analyzed by using a quantitative real time PCR method. : RM 87,900.00 : RM 85,800.00 : RM 36,100.00 Neurosciences Department Conclusions: For the first time, we have been able to describe the occurrence of mtDNA 4,977-bp deletion and decreased mtDNA content in a Malaysian brain tumor population. Deletion of mtDNA 4,977-bp could be classified as pathogenic mutation in connection with mutations in other mitochondrial or nuclear genes as well as environmental factors in the development of various diseases and cancers. We believe that mtDNA 4,977-bp deletion and mtDNA content determination may be considered as potential diagnostic and prognostic biomarker among Malaysian population particularly in those with brain tumors. Yearly Budget Distributed Year 1 Year 2 Year 3 Results: The mtDNA 4,977-bp deletion were observed in 24% (12 out of 50) of our patients. Presence of the ND3 10398A>G mutation did not show significantly correlation with any of the evaluated parameters such as patients age, gender and histological brain tumor types. Moreover, we found that mtDNA copy number was significantly reduced in tumor tissues (13.49+9.32) compared to corresponding blood samples (36.65±9.32). Our study also revealed that 28% of our patients (14 out of 50) were detected to have the 1DH1 c.395G>A (R132H) mutation and a significant association was found with histological tumor types Conclusions: For the first time, we have been able to describe the occurrence of mtDNA 4,977-bp deletion and decreased mtDNA content in a Malaysian brain tumor population. Deletion of mtDNA 4,977-bp could be classified as pathogenic mutation in connection with mutations in other mitochondrial or nuclear genes as well as environmental factors in the development of various diseases and cancers. We believe that mtDNA 4,977-bp deletion and mtDNA content determination may be considered as potential diagnostic and prognostic biomarker among Malaysian population particularly in those with brain tumors.